The Women Question in the Jadid Press of Turkestan in the Early Twentieth Century - Dalieva, Madina Khabibullaevna (The Lingua Spectrum, 2026)
The article examines how the Jadid periodical press in Turkestan (1906–1917) turned the “women question” into a practical agenda of social reform. Drawing on programmatic newspapers and journals (including Taraqqiy, Sadoi Turkiston, and the journal platform Oyina), the study maps major discursive frames: women’s schooling as a precondition for progress; criticism of costly rituals and early marriage; domestic literacy and motherhood as civic competence; and tensions between reformist rhetoric and inherited family morals. The paper combines historical discourse analysis with targeted content analysis and relies on core scholarship on Jadidism and Central Asian history. It argues that print media functioned as a public arena for negotiating new norms, while the modernization project remained non-linear due to censorship, uneven literacy, and competing ideological programs.